Sistem Informasi Anggaran dan Realisasi Kepanitiaan Kegiatan Besar PP. Salafiyah Syafi’iyah Sukorejo Situbondo - Nur Azizah (Department of Science and Technology Ibrahimy University, 2019)
The preparation of budget management is the beginning of the implementation of an Islamic boarding school activity, budget management is used to budget and plan programs from the budget for each pesantren activity carried out by the pesantren committee, so that the pesantren's financial allocations and income can always be well planned. with the management of this budget, it is expected that each committee will be able to plan activities in the years to come. In the implementation of budgeting using a conventional model and reporting of budget realization is still carried out at the end of the implementation so that sometimes there is evidence of use that is not found. Therefore, a financial management system for pesantren activities was built to overcome the problems faced. This system is built using the waterfall method, which in the implementation must be passed step by step so that the system is good. From the results of this study there is an increase in performance in budgeting and reporting of financial realization used. So that it can be said that this system can help facilitate the committee in managing finances.